Managing Service Quality in Akademi Laut Malaysia, Melaka - Mohd Tahir, Ahmad Zahari (1998)
The purpose of this study was to examine the quality of the nonacademic services provided by the Students Affairs Department of Akademi Laut Malaysia (ALAM) in five dimensions, that is tangibles, responsiveness, reliability, assurance and empathy. The study discusses aspects of current service quality theories with focus on the Gap Theory developed by Zeithaml, Berry and Parasuraman. A total of 128 students attending various courses in the first week of August, 1998 were selected to participate in the study. Data collection was done by using the standard service marketing instrument SERVQUAL, developed by Zeithaml, Berry and Parasuraman. Minor modifications however was done to the SERVQUAL instrument to suit the higher education setting. Apart from the SERVQUAL that explored the expectation and perception levels of the students, the researcher had developed a questionnaire soliciting information regarding the overall students' satisfaction level with ALAM services. Data collected were analyzed using the Statistical Package for Social Science (SPSS) program. Descriptive statistic was employed in analyzing the expectations, perceived performance, overall satisfaction level and the gap difference (perceived performance minus expectations). The results of the study revealed negative gap scores for all five dimensions, indicating that the students did not obtain the services as expected. Dimension tangibles was rated poorest in terms of quality of service, followed by empathy, reliability, responsiveness and assurance. In terms of the specific areas, quality of food served was ranked poorest followed by accommodation facility, registration process, cleanliness of the campus and attractiveness of the printed materials such as forms, brochures and pamphlets. The study also shows that the gap score is a reliable indicator to determine the students' overall satisfaction level with the quality of services provided.